Efficient PAPR Reduction in OFDM Signals Using Linear Companding Transform with Inflection Points - C. V. Shilpa, P. Indira Kumari, Ch. Sushmitha Rani (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Large amplitude fluctuations cause serious issues in orthogonal frequency-division multiplexing (OFDM) signals when a nonlinear power amplifier (NLPA) has been utilized. These large amplitude fluctuations are known as peak-to-average power ratio (PAPR), which is a major disadvantage of the OFDM system. To resolve this issue, one must reduce these large amplitude fluctuations in order to achieve higher data rates and improve system performance. A well-known method for reducing the PAPR is the compound transform (CT). It doesn’t have any restrictions on system parameters such as frame format, number of subcarriers, or type of constellation used. Recently, a linear nonsymmetrical companding transform (LNST) has been proposed that has superior performance to transformations based on logarithmic transforms such as µ-law companding. Here, a new linear companding transform (LCT) with Rayleigh distribution (RD) has been implemented with more design ﬂexibility than LNST by introducing two inflexion points. Experimental results show that the proposed transform has a better PAPR reduction and bit error rate (BER) performance than LNST with better power spectral density (PSD).